Redefining and solving the digital divide and exclusion to improve healthcare: going beyond access to include availability, adequacy, acceptability, and affordability - Laronda A. Hollimon; Laronda A. Hollimon; Kayla V. Taylor; Kayla V. Taylor; Rachel Fiegenbaum; Rachel Fiegenbaum; Mary Carrasco; Mary Carrasco; Laurent Garchitorena Gomez; Laurent Garchitorena Gomez; Debbie Chung; Azizi A. Seixas; et al. (Frontiers in Digital Health)
The digital divide in the United States extends beyond the traditional definition of access, which focuses solely on physical infrastructure like broadband networks and connectivity points. This narrow framing has resulted in policies that fail to address the full spectrum of barriers to digital inclusion. To bridge this gap, we propose the Rhizomatic Digital Ecosystem Framework, which emphasizes five interdependent components: access, availability, adequacy, acceptability and affordability. Access highlights the need for physical infrastructure, with programs like the Broadband Equity, Access, and Deployment (BEAD) Program expanding connectivity to underserved areas. Availability ensures the presence of reliable internet infrastructure to meet community needs, with targeted policies like satellite-based solutions addressing challenges in rural and Indigenous areas. Availability policies should focus on federal funding programs like BEAD and the Tribal Broadband Connectivity Program, incentivizing Internet service Providers (ISP) to expand into underserved areas, and leveraging satellite technologies to address infrastructure gaps. Novel policies to address the digital divide include community-owned broadband networks, dynamic spectrum sharing, and blockchain-powered micro-networks to improve availability in underserved areas. Adequacy examines whether internet services meet modern demands, such as telehealth and online education, emphasizing the need for minimum speed standards and performance improvements. Adequacy policies should include enforcing FCC speed standards with regular audits, requiring ISPs to upgrade outdated infrastructure, and providing government grants to improve broadband quality in communities. For adequacy, solutions like AI-driven broadband performance monitoring, funding edge computing in remote regions, and treating broadband as a public utility can enhance internet speed and quality Acceptability tackles cultural and social barriers, including digital literacy gaps, language differences, and technophobia, which can be addressed through localized literacy programs and inclusive design practices. Acceptability policies should prioritize national digital literacy campaigns for underserved groups, mandate inclusive design and accessibility standards, and offer multilingual and culturally relevant resources for digital tools. Affordability addresses financial barriers, as many low-income households struggle to afford monthly internet fees and devices, even with subsidies such as the Affordable Connectivity Program (ACP). To improve acceptability, innovative approaches like universal digital literacy vouchers, gamified education platforms, and mandatory accessibility standards for all digital technologies can ensure equitable and inclusive digital participation. Together, these five dimensions provide a nuanced and actionable framework for crafting effective, interconnected policies and solutions. By addressing each dimension through the lens of the Rhizomatic Digital Ecosystem Framework, policymakers can develop holistic strategies to eliminate the digital divide and foster equitable digital inclusion across all communities.